A review of pathobiological mechanisms and potential application of medicinal plants for vascular aging: focus on endothelial cell senescence (Medical Journal of Indonesia, 2022)
Endothelial cell (EC) senescence plays a pivotal role in aging and is essential for the pathomechanism of aging-related diseases. Drugs targeting cellular senescence, such as senolytic or senomorphic drugs, may prevent aging and age-related diseases, but these bullets remain undeveloped to target EC senescence. Some medicinal plants may have an anti-senescence property but remain undiscovered. Deep learning has become an emerging approach for drug discovery by simply analyzing cellular morphology-based deep learning. This precious tool would be useful for screening the herb candidate in senescent EC rejuvenescence. Of note, several medicinal plants that can be found in Indonesia such as Curcuma longa L., Piper retrofractum, Guazuma ulmifolia Lam, Centella asiatica (L.) Urb., and Garcinia mangostana L. might potentially possess an anti-senescence effect. This review highlighted the importance of targeting EC senescence, the use of deep learning for medicinal plant screening, and some potential anti-senescence plants originating from Indonesia.